2018
DOI: 10.14733/cadaps.2019.496-518
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 3D Solid Modeling Software Libraries for Non-Manifold Modeling

Abstract: In this work, we improved the efficiency and accuracy of our proposed cylinder-based registration and model fitting method of point clouds by terrestrial laser scanners for the as-built modeling of piping systems. Our algorithm simultaneously calculated the scanner parameters and cylinder parameters to avoid the propagation of registration errors and modeling errors. Coarse registration is performed by finding the alignment of the cylinder axes based on the random sample consensus approach and using a hash tab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 17 publications
0
13
0
2
Order By: Relevance
“…The NMT framework presents a formal and consistent relationship among the multi-dimensional constituent entities. The authors' earlier work (Chatzivasileiadi, Wardhana, et al 2018) identified eight entities, namely (sorted in descending order based on the dimensional complexity) Cluster, CellComplex, Cell, Shell, Face, Wire, Edge, and Vertex. The hierarchy of these entities is shown in Figure 1.…”
Section: Non-manifold Topologymentioning
confidence: 99%
See 1 more Smart Citation
“…The NMT framework presents a formal and consistent relationship among the multi-dimensional constituent entities. The authors' earlier work (Chatzivasileiadi, Wardhana, et al 2018) identified eight entities, namely (sorted in descending order based on the dimensional complexity) Cluster, CellComplex, Cell, Shell, Face, Wire, Edge, and Vertex. The hierarchy of these entities is shown in Figure 1.…”
Section: Non-manifold Topologymentioning
confidence: 99%
“…These plugins wrap the classes and functionalities in the core package, as well as provide two-way mechanisms to convert an entity between the geometric representations in the host applications and the topological representations in the library. In an earlier publication (Chatzivasileiadi, Lannon, et al 2018), the authors have presented workflows to use this library in building performance and structural analyses.…”
Section: Non-manifold Topologymentioning
confidence: 99%
“…Although their work deserves appreciation as the first steps of using this method in explicit geological modeling, the authors did not explain the practical details of this approach and offered no explanation for the distinction between using spline surfaces and subdivision surfaces in parametric surface-based geological modeling, especially for non-manifold topology. The term 'Non-manifold' has been used to refer to structures that consist of multiple faces sharing one edge or multiple edges sharing one vertex (Chatzivasileiadi et al 2018). These structures need more complex algorithms for the representations (Rossignac and Cardoze 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Não-manifold é um termo da topologia geométrica que significa permitir que qualquer combinação de arestas, vértices, superfícies e volumes existam em um único corpo lógico [37]. Modelos não-manifold têm uma configuração que não pode ser desdobrada em uma peça plana contínua e, portanto, não são fabricáveis e não são fisicamente realizáveis em um único volume [10].…”
Section: Modelagem Geométricaunclassified
“…Existem muitas outras vantagens oferecidas pelo uso de estruturas de dados topológicas, como eficiência e velocidade no processamento das informações e economia no uso de memória. Nos últimos anos diversos trabalhos têm sido publicados, tais como [6][7][8][9][10][11][12][13][14][15][16], aplicando ou otimizando estruturas de dados topológicas em projetos e pesquisas cientificas.…”
Section: Introductionunclassified